The use of an indirect impact quick-stop mechanism during the turning of α-titanium BT5 alloy. (24th March 2008) - Dahunsi, Olurotimi Akintunde; Awopetu, O.O.
This paper studies the use of an indirect impact quick stop mechanism whose design, construction and mode of operation is relatively simpler in the chip root analysis of α-titanium alloy BT5 in a semi-finish turning operation. The quick-stop was used over a cutting speed range 2?120 m/min, but only micrographs for cutting at 60 m/min were presented, however, the mechanism attained a minimum withdrawal speed of about 3.2 mm/s and an average speed (estimated from the plotted graph) of about 11 m/s. Metallographic analysis of the chip roots presented pronounced Built-Up-Edge (BUE) and segmented chip formation features but the grains varied largely in appearance and shapes. The various chip segments also varied in sizes in contrast to the segments of stainless steel whose chips are usually segmented too.